Gender wage gap in West Germany: how far do gender differences in human capital matter? - Charlotte Lauer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
This paper analyses the extent to which gender differences in human capital contribute to explaining the observable wage differential in favour of men and its reduction since the mid-eighties among West German full-time employees in the private sector. Based on a simple analytical framework, the analysis shows that if a large part of the gender wage gap can be attributed to women?s relative deficit with respect to human capital endowment, an equally large part stems from the fact that female human capital is less valued in terms of wages. The gender wage gap narrowing stems mainly from a reduction in gender inequality with respect to the returns to human capital in terms of wage which favours women. Nevertheless, women improved their relative position regarding human capital endowment, but the overall lower valuation of human capital by the labour market reduces the benefit of this relative improvement. The roles of the educational attainment, labour market experience and occupational factors were analysed specifically. The level of educational attainment explains a large part of the gender wage gap, mainly because women have a lower educational attainment than men but also because similar qualification levels yield lower returns for women. Taken alone, the developments related to education would have increased the gender wage gap significantly. This is because, if women did catch up in terms of educational attainment, the effect of this educational expansion was more than compensated by the fact that the returns to education dropped particularly markedly for women. Changes related to labour market experience have a neutral influence on the gender wage gap. Women improved their relative position concerning their work experience, but lose their advantage in the returns to work experience. Part of the gender wage gap is attributable to occupational segregation, i.e. female crowding into lower paid occupations. The extent of occupational segregation has remained fairly stable, but the wage penalty for working in typically female jobs has increased over time.
Keywords: 330; Frauenarbeitslohn; Lohndifferenzierung; Humankapital; Bildungsertrag; Geschlecht; Arbeitsmarktsegmentierung; Schätzung; Deutschland